Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec - Sucha, Ewa; Silva, Erika; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)

La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.